1984
DOI: 10.1002/pssb.2221260230
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity of Metals with a Superlattice of Voids

Abstract: Superconductivity of metals with a superlattice of vacancy or gas voids is investigated in the preeence of magnetic fields around the second critical field Hc2, At H Hc2 the porous superconductor appears to be a system of an immense number of superconducting regions localized near the voids. The paper represents following results: (i) the dependence of the third critical field Hc3 on the void radius; (ii) the diamagnetic properties of the system; (iii) the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(4 reference statements)
0
3
0
1
Order By: Relevance
“…Надґратниці нанопор впливають на оптичні, механічні, термічні та надпровідні властивості твердих тіл, що представляють інтерес до практичного застосування [65,66].…”
Section: експериментальні дослідження явища просторово-періодичного вunclassified
“…Надґратниці нанопор впливають на оптичні, механічні, термічні та надпровідні властивості твердих тіл, що представляють інтерес до практичного застосування [65,66].…”
Section: експериментальні дослідження явища просторово-періодичного вunclassified
“…Let us consider the magnetic properties of a type-II porous superconductor in a magnetic field higher than the second critical field of the bulk superconductor H c2 . It was shown that at H H c2 surface superconductivity areas arise around voids [26]. Since the Ginsburg-Landau parameter κ 1, interaction of the superconducting currents with the intrinsic magnetic field can be neglected.…”
Section: The Third Critical Field Of a Superconducting Domain Localiz...mentioning
confidence: 99%
“…To calculate the magnetic moment it is necessary to take into account the nonlinear term in the Ginzburg-Landau equation. According to [26] we may present the variation function in the form…”
Section: Diamagnetic Properties Of a Porous Superconductormentioning
confidence: 99%
“…It results in an increase of the third critical field and makes possible channeling of Cooper pairs between voids. In case of the void superlattice the third critical field of the superconductor was determined in [2] and it was shown that the diamagnetic contribution of currents circulating around the voids may be by several orders of magnitude greater than the intrinsic paramagnetic susceptibility of metals.…”
Section: Introductionmentioning
confidence: 99%